FARALDO José M. & Carlos Sanz Díaz (ed.). 2022. La otra Alemania. España y la República Demócrata Alemana (1949-1990). Granada: Comares. - Anna Catharina Hofmann (apropos [Perspektiven auf die Romania], 2023)
Rezension